The Role of Religiosity on The Influence of Muslim Customer Perceived Value To Customer Satisfaction of Islamic Banking - Yayuk Sri Rahayu (IJECA (International Journal of Education and Curriculum Application), 2018)
The successfull of Islamic Banking on the global market depends on the company’s commitment to provide excellent service to their customers. The concept of Muslim customer perceived value (MCPV) is composed of six dimensions that consists of  quality, price, emotional value, social value, Islamic phisical attribute, and Islamic non phisical attribute. The purposes of this research are to determine the influence of MCPV to customer satisfaction of Islamic Banking at Malang Raya dan the role of religiosity in moderating those effects. One hundred and four respondents, who are customers of Islamic Banking, were involved in this research. Accidental sampling was used as sampling technique and instrument was tested by validity and reliability testing. Futhermore, data were analized by moderated regression analysis (MRA). The results of this research shows (1) Simoultaneously, Muslim customer perceived value (MCPV) influences the customer satisfaction and partially, there are only three variables that influence customer satisfaction such as price, social value, and Islamic non phisical attribute. Other variables such as quality, emotional value, and Islamic phisical attribute does not influence customer satisfaction; (2) Religiosity as a moderating variable on the influence Islamic non phisical attribute to the customer satisfaction. The moderating effect is streghtening the existing influence.